1998
DOI: 10.1007/s005950050302
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Prostaglandin E 1 on Ischemic Colitis Following Surgery on the Abdominal Aorta

Abstract: To determine the effects of prostaglandin E1 (PGE1) on the intestinal circulation, an experimental dog model of ischemic colitis following abdominal aortic reconstruction was made by ligating the inferior mesenteric artery (IMA) and the internal iliac artery, with the creation of a 50% stenosis in the superior mesenteric artery (SMA). The parameters of enteric ischemia included the blood flow of the SMA, the tissue blood flow in the small intestine and left colon, the mean stump pressure of the IMA (IMAP), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…However, the treatment was not effective and the following colonoscopy showed that the patient's condition had worsened. Other reports describe the effect of PGE1 (intra‐arterial or intravenous injection) in increasing colonic blood flow 18–20 . In our case, the patient's lesion and symptoms improved progressively after we started intravenous injection of PGE1.…”
Section: Discussionsupporting
confidence: 47%
“…However, the treatment was not effective and the following colonoscopy showed that the patient's condition had worsened. Other reports describe the effect of PGE1 (intra‐arterial or intravenous injection) in increasing colonic blood flow 18–20 . In our case, the patient's lesion and symptoms improved progressively after we started intravenous injection of PGE1.…”
Section: Discussionsupporting
confidence: 47%
“…PGE1 has been used to treat ischemic liver damage, 28 ischemic colitis, 29 and cerebral ischemia. 30 However, there were little reports on acute AAN treatment with PGE1.…”
Section: Discussionmentioning
confidence: 99%
“…Ob eine Patientenselektion bei intraoperativem Monitoring mit dopplerflowmetrischen Verfahren einen Vorteil bringen würde, bedarf der Überprüfung (8). Tierexperimentellen Befunden zufolge wäre die Testung der protektiven Effekte von Prostaglandin E1 auch beim Menschen zur Verhinderung der Kolonischämie nach aortaler Chirurgie angezeigt (7).…”
Section: Apparative Untersuchungenunclassified